Pengaruh Profitabilitas, Solvabilitas, dan Opini Audit terhadap Audit Delay pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Yunita, Feronika; Keristin, Usnia Wati (LITERATUS, 2025)
Financial reports are an important instrument in assessing performance. Every company listed on the Indonesia Stock Exchange (IDX) is required to publish and submit to the Financial Services Authority (OJK). This study aims to determine the Effect of Profitability, Solvency, Company Size, Audit Committee and Audit Opinion on Audit Delay in Property and Real Estate companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The approach used in this study is a quantitative approach. The sample in this study consisted of 24 companies using purposive sampling techniques. The data analysis techniques used are descriptive statistics, classical assumption tests, and hypothesis tests using multiple linear regression analysis. The results of this study indicate that the variables Profitability, Solvency have no effect on Audit Delay, while Audit Opinion has a positive effect on Audit Delay. And the results of the determination coefficient test show a number of 0.358, this indicates that the variables simultaneously independent Profitability, Solvency and Audit Opinion are able to explain Audit Delay which is the dependent variable as much as 35.8%, while the remaining 64.2% is explained by other variables.